2014
DOI: 10.1111/jsm.12590
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function in the Late Postmenopause: A Decade of Follow-Up in a Population-Based Cohort of Australian Women

Abstract: Introduction There is a paucity of longitudinal studies assessing sexual function of women in the late postmenopause. Aim This study aims to describe sexual function of women in the late postmenopause and to investigate change from early postmenopause. Methods Cross-sectional analysis of 2012/13 and longitudinal analysis from 2002/04 of the population based, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 32 publications
2
29
0
6
Order By: Relevance
“…(12) Silva et al [48] in their study on 195 women reported that postmenopausal women with metabolic syndrome present more frequently with sexual dysfunctions compared with those without metabolic syndrome. (13) Lonnèe-Hoffmann et al [49] in their study on 230 women demonstrated that during the late postmenopausal period half of the women were sexually active, with the most important interpreters being partner availability and absence of depression. Compared with early postmenopausal women, the sexual function scores had dropped overall but were stable for sexually active women.…”
Section: Female Sexual Changesmentioning
confidence: 96%
“…(12) Silva et al [48] in their study on 195 women reported that postmenopausal women with metabolic syndrome present more frequently with sexual dysfunctions compared with those without metabolic syndrome. (13) Lonnèe-Hoffmann et al [49] in their study on 230 women demonstrated that during the late postmenopausal period half of the women were sexually active, with the most important interpreters being partner availability and absence of depression. Compared with early postmenopausal women, the sexual function scores had dropped overall but were stable for sexually active women.…”
Section: Female Sexual Changesmentioning
confidence: 96%
“…Essas mudanças podem resultar em significativas disfunções sexuais e repercussões para o funcionamento sexual de muitas mulheres, afetando a sexualidade das mesmas. Desse modo, essa categoria está composta por 12 artigos que em comum possuem o intuito de avaliar a função sexual das mulheres após a menopausa (Cabral et al, 2012;Cavalcanti, Farias, Ithamar, Silva, & Lemos, 2014;Dennerstein, Koochaki, Barton, & Graziottin, 2006;Erenel, Golbasi, Kavlak, & Dilbaz, 2015;Graziottin, 2007;Graziottin, Koochaki, Rodenberg, & Dennerstein, 2009;Hayes et al, 2008;Lonnèe-Hoffmann, Dennerstein, Lehert, & Szoeke, 2014;Polizer, & Alves, 2008;Silva, Lima, & Moraes, 2013;Thompson et al, 2011;Valadares et al, 2008).…”
Section: Função Sexual Após a Menopausa E Fatores Associados àS Disfuunclassified
“…Nota-se entre a maioria dos estudos o reconhecimento das possíveis influências destas disfunções sexuais para a vida das mulheres e a influência dos sintomas da menopausa para a acentuação destas disfunções, cuja finalidade é respaldar a prática clínica e proporcionar maiores informações e recursos interventivos adequados para as mulheres acometidas por tais dificuldades (Lonnèe-Hoffmann et al, 2014). Assim, os níveis de satisfação em relação à sexualidade também foram avaliados, visto que esse aspecto está interligado à função sexual (Polizer, & Alves, 2008;Thompson et al, 2011).…”
Section: Função Sexual Após a Menopausa E Fatores Associados àS Disfuunclassified
See 2 more Smart Citations